2020
DOI: 10.3390/ijerph17238868
|View full text |Cite
|
Sign up to set email alerts
|

Small Subcutaneous Soft Tissue Tumors (<5 cm) Can Be Sarcomas and Contrast-Enhanced Ultrasound (CEUS) Is Useful to Identify Potentially Malignant Masses

Abstract: Subcutaneous masses smaller than 5 cm can be malignant, in contrast with the international guidelines. Ultrasound (US) and magnetic resonance imaging (MRI) are useful to distinguish a potentially malignant mass from the numerous benign soft tissue (ST) lesions. Contrast-enhanced ultrasound (CEUS) was applied in ST tumors, without distinguishing the subcutaneous from the deep lesions. We evaluated CEUS and MRI accuracy in comparison to histology in differentiating malignant from nonmalignant superficial ST mass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…STTs were assigned to different perfusion patterns via a qualitative classification and differentiated between benign and malignant. Benign tumors showed no perfusion or homogeneous perfusion patterns, whereas malignant tumors often showed inhomogeneous and strong contrast enhancement with central areas of necrosis correlating with MRI imaging [13,15,16]. It could be demonstrated that CEUS can contribute to a faster and more precise STT assessment with high discrimination accuracy [15,17].…”
Section: Discussionmentioning
confidence: 74%
“…STTs were assigned to different perfusion patterns via a qualitative classification and differentiated between benign and malignant. Benign tumors showed no perfusion or homogeneous perfusion patterns, whereas malignant tumors often showed inhomogeneous and strong contrast enhancement with central areas of necrosis correlating with MRI imaging [13,15,16]. It could be demonstrated that CEUS can contribute to a faster and more precise STT assessment with high discrimination accuracy [15,17].…”
Section: Discussionmentioning
confidence: 74%
“…In soft tissue sarcomas, tumour size and location relative to the fascia are important for assessing malignancy risk [14]. While studies show that size ≥ 5 cm and increased age are main risk factors [7,15,32], even smaller lesions can be malignant [8], leading to recommendations for core needle biopsies in tumours ≥ 3 cm [23,31]. Importantly, in our study there was a relevant discrepancy of the suspected and the histopathologically-confirmed diagnosis, which in 6 cases lead to a malignant tumour diagnosis of a mass primarily considered benign (2.1% of total true tumours).…”
Section: Soft Tissue Sarcomamentioning
confidence: 99%
“…In addition, quantitative CEUS allows precise assessment of microcirculatory perfusion, as a surrogate parameter for tissue viability and metabolism, and objectively monitoring the progression of postoperative microcirculatory changes. Furthermore, CEUS is also expected to be an additional diagnostic tool for predicting the malignant potential of bone tumors, due to varying enhancement patterns [ 51 ]. Hence, CEUS not only allows for early identification and initial treatment of patients with related injuries but is also expected to be used to monitor the process of blood flow reconstruction, thus facilitating the postoperative rehabilitation of patients.…”
Section: Applications and Insights Of Nucas Of The Musculoskeletal Sy...mentioning
confidence: 99%